1991
DOI: 10.1161/01.atv.11.3.495
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interleukin-1 on lipid metabolism in the rat. Similarities to and differences from tumor necrosis factor.

Abstract: Infection and inflammation are associated with hypertriglyceridemia, which is thought to be mediated by cytokines. Previous studies at our laboratory and others have shown that tumor necrosis factor acutely increases serum triglyceride levels primarily by stimulating hepatic lipid synthesis and secretion. The role of interleukin-1 (IL-1), a cytokine that is also secreted by stimulated macrophages and that has many actions that overlap those of tumor necrosis factor, has not been studied in depth. The present s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 47 publications
4
58
0
1
Order By: Relevance
“…We previously showed that these cytokines stimulate hepatic fatty acid and cholesterol synthesis and increase VLDL production and secretion. [25][26][27] Like LPS, these cytokines also inhibit cholesterol 7␣-hydroxylase in the liver and lipoprotein lipase activity in adipose tissue. 7,28 In the present study, IL-1 administration increased both SPT activity (50% to 80%) and mRNA levels (2-fold to 3-fold) in the liver of Syrian hamsters; however, TNF had no such effect on SPT activity or mRNA levels in intact animals.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that these cytokines stimulate hepatic fatty acid and cholesterol synthesis and increase VLDL production and secretion. [25][26][27] Like LPS, these cytokines also inhibit cholesterol 7␣-hydroxylase in the liver and lipoprotein lipase activity in adipose tissue. 7,28 In the present study, IL-1 administration increased both SPT activity (50% to 80%) and mRNA levels (2-fold to 3-fold) in the liver of Syrian hamsters; however, TNF had no such effect on SPT activity or mRNA levels in intact animals.…”
Section: Discussionmentioning
confidence: 99%
“…A close interaction has been described between the innate immune system and lipoprotein metabolism in general and in triglyceride (TG) metabolism in particular ( 6 ). This interaction has largely been derived from studies that evaluated the effects of lipopolysaccharide (LPS), a major component of the cell wall of gram-negative bacteria, and individual cytokines on lipoprotein metabolism (7)(8)(9).…”
Section: H]oleate [Triolein (To)] and [mentioning
confidence: 99%
“…Among these, changes in lipid metabolism have received much attention due to the link between infection/inflammatory diseases and atherosclerosis (2)(3)(4)(5)(6). The characteristic changes in lipid metabolism during the APR include hypertriglyceridemia (7), decreases in serum high density lipoprotein cholesterol levels (8,9), increased hepatic cholesterol synthesis, inhibition of bile acid synthesis (10), increased hepatic fatty acid synthesis, and decreased hepatic fatty acid oxidation and ketogenesis (11,12). These changes are mediated by alterations in gene expression caused by proinflammatory cytokines including TNF␣, IL-1␤, and IL-6 (10).…”
mentioning
confidence: 99%